Muscle structure predictors of vertical jump performance in elite male volleyball players: a cross-sectional study based on ultrasonography - Jiang, W.; Chen, C.; Xu, Y. (Frontiers in Physiology, 2024)
Objective The objective of this investigation is to examine the contribution of key muscle groups in the lower limbs to vertical jumping performance in elite male volleyball players. Specifically, the study focuses on the rectus femoris (RF), vastus lateralis (VL), and lateral gastrocnemius (LG), as well as exploring differences between attack jump and other vertical jump types.